Assembly of Hexagonal Column Interpenetrated Spheres from Plant Polyphenol/Cationic Surfactants and Their Application as Antimicrobial Molecular Banks. Issue 6 (17th December 2021) - Shen, Yutan; Li, Shikun; Qi, Ruilian; Wu, Chunxian; Yang, Ming; Wang, Jie; Cai, Zhuojun; Liu, Kaiang; Yue, Jiling; Guan, Bo; Han, Yuchun; Wang, Shu; et al.
Abstract: Microbial infections have become a great threat to human health and one of the main risks arises from direct contact with the surfaces contaminated by pathogenic microbes. Herein, a kind of hexagonal column interpenetrated spheres (HCISs) are fabricated by non‐covalent assembly of plant gallic acid with quaternary ammonium surfactants. Different from one‐time burst release of conventional antimicrobial agents, the HCIS acts like a "antimicrobial molecular bank" and releases the antimicrobial ingredients in a multistage way, leading to long‐lasting antimicrobial performance. Taking advantage of strong hydrophobicity and adhesion, HCISs are applicable to various substrates and endowed with anti‐water washing property, thus showing high in vitro antimicrobial efficiency (>99 %) even after being used for 10 cycles. Meanwhile, HCISs exhibit broad‐spectrum antimicrobial activity against bacteria and fungi, and have good biocompatibility with mammalian cells. Such a low‐cost and portable long‐lasting antimicrobial agent meets the growing anti‐infection demand in public spaces. Abstract : Long‐lasting and broad‐spectrum antimicrobial agents with the special structure of hexagonal column interpenetrated spheres (HCISs) are constructed through non‐covalent assembly of plant gallic acid and quaternary ammonium surfactants. HCISs possess high substrate‐adhesion on various substrates and high anti‐water washing property, and can continuously provide antimicrobial ingredients in a multistage way, avoiding one‐time burst release of antimicrobial units.